Pelatihan praktik pengolahan sampah dengan metode 3R di SDN 03 Putat Nutug Ciseeng Bogor - Zakirman Zakirman; Titi Chandrawati; Gusti Nurdin; Ngadi Marsinah (Universitas Hamzanwadi, 2022)
Household waste continues to grow daily, forcing the Indonesian government to start thinking about a good management strategy that will not damage the environment or harm the community. A two-fold increase in waste is very likely to occur if there are no strict policies for waste that result in environmental and ecosystem pollution. Waste is not only a big city problem. Each district/city in each province has the same problems in handling waste. For example, in Bogor Regency, approximately 2,800 tons of waste must be managed and transported daily. However, only about 700 tons of waste can be transported and managed by the local government. This condition was also found at SDN Putat Nutug, Bogor Regency. Waste management at SDN Putat Nutug 03 Ciseeng, Bogor Regency, still relies on traditional methods, namely burning. Garbage-burning activities that do not comply with this procedure can cause problems such as air pollution. This community service activity aims to increase students' knowledge and skills through hands-on sorting, processing, and managing waste. The practical activities of waste processing are divided into two parts: the presentation of theory and education regarding waste and how to process it and the practical activities of waste processing with the 3R method. The activity results in environmentally friendly products from plastic waste, showing that the 3R method interests’ students. Hopefully, in the future, schools that apply the 3R method will increase the method of waste management so that the waste problem can be reduced slowly